2009
DOI: 10.1016/j.intell.2008.11.005
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of laboratory and clinical working memory tests and their prediction of fluid intelligence

Abstract: The working memory (WM) construct is conceptualized similarly across domains of psychology, yet the methods used to measure WM function vary widely. The present study examined the relationship between WM measures used in the laboratory and those used in applied settings. A large sample of undergraduates completed three laboratory-based WM measures (operation span, listening span, and n-back), as well as the WM subtests from the Wechsler Adult Intelligence Scale-III and the Wechsler Memory Scale-III. Performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
91
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(102 citation statements)
references
References 73 publications
8
91
1
2
Order By: Relevance
“…Letter-number sequencing subtest of the Wechsler Adult Intelligence Scale -III (WAIS-III; Wechsler, 1997) The Letter-Number Sequencing (LNS) subtest is a measure of verbal working memory and constitutes a good predictor of fluid intelligence (Shelton et al, 2009). We decided to control for working memory, in view of its role in future projection (Heerey et al, 2011) and its association with apathy in schizophrenia (Faerden et al, 2009).…”
Section: Apathy and Clinical Measuresmentioning
confidence: 99%
“…Letter-number sequencing subtest of the Wechsler Adult Intelligence Scale -III (WAIS-III; Wechsler, 1997) The Letter-Number Sequencing (LNS) subtest is a measure of verbal working memory and constitutes a good predictor of fluid intelligence (Shelton et al, 2009). We decided to control for working memory, in view of its role in future projection (Heerey et al, 2011) and its association with apathy in schizophrenia (Faerden et al, 2009).…”
Section: Apathy and Clinical Measuresmentioning
confidence: 99%
“…We considered two WM tasks-digit span of the Wechsler Adult Intelligence Scale-Fourth Edition (WAIS-IV; Wechsler, 2008), a measure for immediate memory span, to represent simple WM, because it possesses only the storage component (Shelton, Elliott, Hill, Calamia, & Gouvier, 2009) that requires maintaining information over a short period (Unsworth, & Engle, 2007). A note about the digit-span task-it consists of two components, forward and backward spans.…”
mentioning
confidence: 99%
“…It has therefore been suggested that the backward condition is dependent on the phonological loop and the central executive, which is reflected in the form of greater activation of additional prefrontal and frontal areas bilaterally (Li, Qin, Zhang, Jiang, & Yu, 2012). Despite these evidences, several studies show that both spans significantly account for the storage component (Bowden, Petrauskas, Bardenhagen, Meade, & Simpson, 2013;Shelton et al, 2009;Wilde, Strauss, & Tulsky, 2004). In the current study, the two components were analyzed separately to check for handedness differences, if any.…”
mentioning
confidence: 99%
“…Por outro lado, Shelton e colaboradores (2009) afirmam que as características da tarefa N-back são potencialmente boas como medida de MT e encontraram em seu estudo uma convergência entre a tarefa N-back e outros instrumentos utilizados no contexto clínico, como a tarefa Sequência de Números e Letras, Aritmética e Span de dígitos (Shelton et al, 2009). Miller e colaboradores (2009), apesar de não concordarem com o uso da tarefa N-back no contexto clínico, comentam que ela foi a úni-ca das atividades de seu experimento capaz de identificar diferenças cognitivas entre idosos com doença de parkin-son e indivíduos controles.…”
unclassified